A critical review of sudden unexpected deaths at Tygerberg Hospital Forensic Pathology Laboratory over a one-year period in 2016 - Roman, Jill (Stellenbosch : Stellenbosch University, 2021)
Thesis (MMed)--Stellenbosch University, 2021.